Some T2 Terrace Soils of Peninsular Malaysia: I. Micromorphology, Genesis and Classification - Jusop, Shamsuddin; Tessens, Eddy (1983)
18 profiles belonging to 14 soil series of the Tz terrace soils of Peninsular Malaysia were studied. The soils are derived from alluvial materials of mixed origin of Holocene age. They are mainly Inceptisols. Others are classified as Entisols, Ultisols and Alfisols. The study indicates that the soils are either in the recent or intermediate stage of weathering. The c/f related distribution is gefuric in the sandy families, gefuric and/or chitonic in the coarse loamy families, and porphyric in the fine loamy and the clayey families. It is found that phytoliths are more common in the east than in the west coast of the peninsula-